Prevalence and prognostic role of thoracic lymphadenopathy in Covid-19 = Prävalenz und prognostische Rolle der thorakalen Lymphadenopathie bei Covid-19 - Bucher, Andreas; Sieren, Malte Maria; Meinel, Felix Gabriel; Klöckner, Roman Trutz; Fink, Matthias A.; Sähn, Marwin-Jonathan; Wienke, Andreas (RöFo, 2025)
Purpose: The prevalent coronavirus disease 2019 (COVID-19) pandemic has spread throughout the world and is considered a serious threat to global health. The prognostic role of thoracic lymphadenopathy in COVID-19 is unclear. The aim of the present meta-analysis was to analyze the prognostic role of thoracic lymphadenopathy for the prediction of 30-day mortality in patients with COVID-19. Materials and Methods: The MEDLINE library, Cochrane, and SCOPUS databases were screened for associations between CT-defined features and mortality in COVID-19 patients up to June 2021. In total, 21 studies were included in the present analysis. The quality of the included studies was assessed by the Newcastle-Ottawa Scale. The meta-analysis was performed using RevMan 5.3. Heterogeneity was calculated by means of the inconsistency index I2. DerSimonian and Laird random-effect models with inverse variance weights were performed without any further correction. Results: The included studies comprised 4621 patients. The prevalence of thoracic lymphadenopathy varied between 1% and 73.4%. The pooled prevalence was 16.7%, 95% CI=(15.6%; 17.8%). The hospital mortality was higher in patients with thoracic lymphadenopathy (34.7%) than in patients without (20.0%). The pooled odds ratio for the influence of thoracic lymphadenopathy on mortality was 2.13 (95% CI=[1.80–2.52], p<0.001). Conclusion: The prevalence of thoracic lymphadenopathy in COVID-19 is 16.7%. The presence of thoracic lymphadenopathy is associated with an approximately twofold increase in the risk for hospital mortality in COVID-19.
Online veröffentlicht: 22. Juli 2024